Well-being and Resilience on Higher Education: A Systematic Literature - Khaira, Nurul; Sayekti, Andita (Universitas Airlangga, 2024)
Well-being and resilience are problems that often arise in various circles, including students and lecturers in higher education. This is due to pressure from both internal and external factors experienced. This research used 10 selected journals from a total of 679 articles found related to well-being and resilience in higher education in searches using the Scopus and ProQuest websites. Then a screening was carried out using the PRISMA-P method related to well-being, resilience, and higher education in the last 10 years. This research aims to determine the methods used to measure the well-being and resilience of lecturers and students. The results of this research explain that the methods that can be applied include quantitative research using analysis of variance (ANOVA) or Structural Equation Modeling (SEM) methods and qualitative research using interviews, focus group discussions, Stress Management and Relaxation Techniques (SMART), Mindfulness Training, and Coteaching Model. The advice researchers give for further research is to research what factors can influence well-being and resilience in higher education.